2013
DOI: 10.1134/s0021364012230051
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature diamond-like Si-based ferromagnet with self-organized superlattice distribution of Mn impurity

Abstract: Crystal structure of Si:Mn diluted magnetic semiconductor with Curie temperature 500К, deposited from laser plasma on GaAs(100) substrates, was investigated by high-resolution transmission electronic microscopy and diffraction. This laser technology allows to reach of solid solution of 15%Mn in silicon with high electrical and full magnetic activity, conservation of diamondlike crystal structure and epitaxy growth of Si:Mn. The self-organized formation of superlattice structures takes place with period equal t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…The Mn impurity in it has the high electric and magnetic activity. The direct evidence of the ordered structure of the layers of the diluted magnetic semiconductor Si:Mn/GaAs was presented earlier [3], which was obtained using high resolution transmis sion electron microscopy and local electron diffrac tion. The self organized formation of the superlattice structure with the period of the triple distance between the nearest atomic layers (110) and the interval between layers (110) doped with Mn atoms and ori ented along the growth direction of the Si:Mn film was found.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…The Mn impurity in it has the high electric and magnetic activity. The direct evidence of the ordered structure of the layers of the diluted magnetic semiconductor Si:Mn/GaAs was presented earlier [3], which was obtained using high resolution transmis sion electron microscopy and local electron diffrac tion. The self organized formation of the superlattice structure with the period of the triple distance between the nearest atomic layers (110) and the interval between layers (110) doped with Mn atoms and ori ented along the growth direction of the Si:Mn film was found.…”
mentioning
confidence: 98%
“…There were repeated attempts to synthesize the ferro magnetic diluted magnetic semiconductor on the basis of silicon doped with 3d impurities [3]. The highest temperature diluted magnetic semiconductors on the basis of diamond like semiconductors were synthe sized in our laboratory by pulse deposition from a laser plasma [3][4][5][6]. It was demonstrated that such strongly nonequilibrium technology can be used to synthesize thin (30-200 nm) GaSb:Mn and InSb:Mn layers with the Curie temperature T C above 500 K and Ge:Mn, Si:Mn, and Si:Fe layers with the Curie temperatures of 400, 500, and 250 K, respectively, on single crystal GaAs, Si, and sapphire (Al 2 O 3 ) substrates.…”
mentioning
confidence: 99%
See 3 more Smart Citations